Os pressupostos da tutela antecipada como textos normativos abertos e a função do precedente judicial na sua aplicação - Almeida, Bruno Carneiro da Cunha (2015)
The study has as its main object the legislative technique used in formulating the assumptions of preliminary injunction. Recently, the legal thinking has undergone several transformations, among which stands out the very legislative technique. Increasingly, there is room for open normative texts, purposely indeterminate in order to provide greater flexibility and adaptability to the legal system. In this context is inserted the issue of preliminary injunction, whose legal requirements are written in vague and indeterminate language. This indeterminate character provides greater complexity in the application process of injunctive relief, falling short subsumption of the method in its decision-making process. Hence the concern to ensure equality and legal certainty in the application of the preliminary injunction, in order to inhibit unwanted lottery law. As a result, the precedent plays role in normative definition of the assumptions of preliminary injunction, bringing the group's method of cases in this application.